Analysis of the application of professional nursing care to the team method and work stress of nurses in the hospital - Savitri, Anggita Rahma; Widiyanto, Puguh; Suhariyanti, Enik (Borobudur Nursing Review, 2021)
Background : Nurse uses some nursing care models during nursing process based on hospital policy. One of the models is team-base care. However, this model has some disadvantages and can lead work-related stress among nurses. When the work-related stress is out of control, it can cause decreasing in quality of nursing care. Objective : The aim of this study was to determine relationship between profesional team nursing care method and work-related stress among nursing in RSUD Muntilan in year 2020. Methods : This study was used a descriptive cross-sectional study design. Sample in this study was 128 participants using total sampling. To measure the variables, this study was used profesional team nursing care method questionnaire and nursing work stress questionnaire. The Spearmen-Rank test was used in this study for the bivariate analysis. Results : This study found that there was a relationship between between profesional team nursing care method and work-related stress among nursing in RSUD Muntilan (p-value 0.001; r -0.384). In this study, when nurses implemented profesional team nursing care method, nurses would have less work-related stress. Conclusion : Nurses and other health care providers can recognize related factors of work-related stress among nurses in hospital. Thus, the evaluation process related to nurse’s works should be considered the type of nursing care method that used in ward.